Clinical study of non epidermoid malignancies of the paranasal sinuses - Prabhakar Rao, Y.; Amreeta Kaur, Punga (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Malignancy of paranasal sinuses post challenging issues not only for surgeons but also for radiologists. Patients also try to avoid and neglect the condition. Hence clinical studies are more pertinent on this issue. Objective was to study clinical picture of non epidermoid malignancies of the paranasal sinuses. Methods: This was a retrospective hospital based study of 30 patients with non epidermoid malignancies of the paranasal sinuses from two hospitals over a period of more than four years. Clinical characteristics were studied. CT scan, diagnostic nasal endoscopy, histopathology was done for all patients. Data was analyzed using proportions. Results: Majority affected were males. The male to female ratio was 2:1. Maximum cases were found in the age group of 51-60 years and all of them were males. Left side was most commonly affected. The most common presenting feature was nasal obstruction in 50% of the cases. Nasal endoscopy findings has shown that there were five cases each of pinkish red polypoid mass, pinkish grey fleshy mass, pinkish red proliferative mass, pink fleshy mass, purulent discharge and fleshy pinkish red mass. Heterogeneous soft tissue density was the most common CT scan finding. Non Hodgkins lymphoma was more common. Half of the cases were managed by maxillectomy and half of the cases were managed by radiotherapy. There was no recurrence of the tumor after 6-9 months of follow up. Conclusions: Males are more commonly affected than females. Appropriate management of cases prevents recurrence of the tumors.